Frequency of Congenital Cardiac Conditions in Children Born to Diabetic Moms - Hamid Iqbal, Saeed Ur Rehman, Abdurrazaq, Ali Abbas Khan, Mazhar Ali, Fawad Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The foetal cardiovascular system is teratogenically affected by maternal diabetes. Because of this, cardiovascular abnormalities are the most prevalent anomaly in children of diabetes moms. Despite improvements in the medical care provided during pregnancy to diabetic mothers, a cardiac complication in their infants is still more frequent than in infants of the general population. Objectives: to quantify the prevalence of congenital cardiac problems in offspring of diabetes moms. Materials & Methods: this-Cross-sectional-study conducted in the Departments of Paediatrics and Neonatology, Ayub Medical College and Hospital, Abbottabad . from Jan 7 2021, to Jun 6 2021. A total of 111 full-term neonates born to diabetic mothers were included. Premature babies and other congenital anomalies were excluded. After taking consent and detailed history, all the neonates included in the study were sent for (Echocardiography) at the cardiac division of Abbottabad's Ayub Teaching Hospital. In the same department, echocardiography was conducted by the same cardiologist. Neonatal congenital heart disease was treated in hospitals. Results: Mean age was 3.35 ± 1.29 days (Table I). The mean maternal age was 38.64 ± 1.37 weeks. Out of the 111 patients, 79 (71.17%) were male, and Females made up 32 (28.19%), with a male-to-female ratio of 2.5:1. The average newborn weighed 3.93 1.62 kg. In this research, I discovered that 43 (38.74%) children with a mother who has diabetes had congenital cardiac disease. Conclusion: This study has shown the prevalence of congenital cardiac abnormalities, with patent ductus arteriosus being the most prevalent abnormality among children born to diabetic moms. Keywords: congenital heart defects, diabetic mothers, patent ductus arteriosus. Births in the US, whereas just 2% of pregnancies in Faisalabad have diabetes.Teratogenic